Seminars in general adult psychiatry - Kingdon, David G.; Rowlands, Paul (Psychiatrist); Stein, George (College seminars series, 2024)
This long-awaited third edition of Seminars in General Adult Psychiatry provides a highly readable and comprehensive account of modern general adult psychiatry. The text has been fully updated throughout by leading figures in modern psychiatry. This new edition covers developments in the understanding of mental disorders, service delivery, changes to risk assessment and management, collaborate care plans and 'trauma-informed' care. Coverage will also be given to the implementation of the ICD-11 and DSM-5 classification systems, and the impact on diagnosis and treatment. Key features of the previous edition that have been updated include the detailed clinical descriptions of psychiatric disorders and historical sections with access to the classic studies of psychiatry. Additional topics include autism, ADHD and physical health. This is a key text for psychiatric trainees studying for their MRCPsych exams, and a source of continuing professional development for psychiatrists and other mental health professionals